Dulaglutide is an effective treatment for lowering HbA1c in patients with type 2 diabetes regardless of body mass index. Issue 12 (28th August 2019) - Gentilella, Raffaella; Sesti, Giorgio; Vazquez, Luis; Sapin, Hélène; Reed, Victoria; Romera, Irene; Pozzilli, Paolo
Abstract: Aim: To assess the relationship between baseline body mass index (BMI) and glycaemic control in dulaglutide‐treated patients, a post hoc analysis was conducted on HbA1c and baseline BMI data from eight AWARD studies, with a total of 5770 patients. Materials and methods: Changes from baseline in HbA1c data from patients treated with 1.5 mg or 0.75 mg dulaglutide, active comparator or placebo, were analyzed in each study (AWARD‐1 to −6, −8 and − 9) at approximately 6 months (26, 24 and 28 weeks, respectively). Within each study, data were analyzed by the following baseline BMI categories: <30, ≥30 to <35, and ≥ 35 kg/m 2 . Results: In this post hoc analysis, 1.5 mg or 0.75 mg dulaglutide treatment achieved statistically significant HbA1c reductions from baseline in all BMI categories (least‐squares mean change from −0.62 to −1.75%) across the AWARD studies. No statistically significant treatment‐by‐BMI category interactions were found for reductions in HbA1c. Conclusion: This post hoc analysis of eight AWARD studies indicates that baseline BMI does not affect the relative treatment efficacy of dulaglutide as measured by HbA1c change from baseline in any study. Dulaglutide is an effective treatment option for adult patients with type 2 diabetes regardless of their baseline BMI category.